Hvem? Hvor mange? En migrasjonsetikk for Norge - Eikrem, Asle (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
In a world marked by surging international conflicts, labour market globalisation, ever-widening economic inequities, steady improvement in the flow of information, and increasing possibilities for mobility over greater distances, the number of migrants on a worldwide basis is hardly likely to decrease in coming years. Immigration regulations are devised within a confluence of national interests, international laws, and attention to migrants' individual rights. The tension between these disparate considerations begs the question: How can we best safeguard both universal rights issues and European economic integration, as well as the Norwegian state's obligation, vis-à-vis the distribution of benefits, to its own citizens. We are moving into extremely complex ethical and legal territory, where there are no easy answers. In this book, the author puts Norway's immigration policy under a moral-philosophical loupe for a thorough analysis of various answers to key questions in the Norwegian immigration debate. This book is aimed at anyone interested in immigration policy issues, but especially persons working professionally in the field, such as political philosophers, politicians, lawyers, case managers and political scientists.